2008
DOI: 10.2174/1874082000802010041
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Circuitries Underlying Two Types of Peripheral Autonomic Nervous System Disorders~!2008-04-24~!2008-09-26~!2008-12-05~!

Abstract: Abstract:The assessment of circulating neurotransmitters: noradrenaline, adrenaline, dopamine, platelet serotonin, plasma serotonin and plasma tryptophan before and after many types of stressor agents and neuropharmacological drugs carried out over the last thirty years allowed us to accumulate information dealing with the central nervous system (CNS) versus the peripheral autonomic nervous system (ANS) interactions in healthy as well as diseased mammals. Furthermore, the accurate knowledge about the CNS circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 113 publications
3
23
0
Order By: Relevance
“…[16][17][18] In addition, both sympathetic branches of the peripheral ANS depend on the A 5 pontomedullary nucleus that releases noradrenaline (NA) 19 and the C 1 medullary nuclei which secrete adrenaline (Ad). [20][21][22][23][24] Furthermore, both CNS nuclei interchange direct inhibitory axons whose neurotransmitters act at post-synaptic alpha-2 receptors, which crowd both nuclei. [18][19][20][21][22][23][24][25] Finally, experimental evidence has demonstrated that secretion of both peripheral hormones (insulin and glucagon) would depend on the interaction between two opposite neuroendocrine circuits.…”
Section: Dovepressmentioning
confidence: 99%
See 4 more Smart Citations
“…[16][17][18] In addition, both sympathetic branches of the peripheral ANS depend on the A 5 pontomedullary nucleus that releases noradrenaline (NA) 19 and the C 1 medullary nuclei which secrete adrenaline (Ad). [20][21][22][23][24] Furthermore, both CNS nuclei interchange direct inhibitory axons whose neurotransmitters act at post-synaptic alpha-2 receptors, which crowd both nuclei. [18][19][20][21][22][23][24][25] Finally, experimental evidence has demonstrated that secretion of both peripheral hormones (insulin and glucagon) would depend on the interaction between two opposite neuroendocrine circuits.…”
Section: Dovepressmentioning
confidence: 99%
“…[20][21][22][23][24] Furthermore, both CNS nuclei interchange direct inhibitory axons whose neurotransmitters act at post-synaptic alpha-2 receptors, which crowd both nuclei. [18][19][20][21][22][23][24][25] Finally, experimental evidence has demonstrated that secretion of both peripheral hormones (insulin and glucagon) would depend on the interaction between two opposite neuroendocrine circuits. According to the above, we decided to investigate the effect of amantadine, a glutamic acid (N-methyl-D-aspartate [NMDA]) antagonist, which inhibits the C 1 (Ad) but not the A 5 (NA) nuclei, and provokes absolute reduction of plasma adrenaline concentration when administered to normal subjects during fasting conditions.…”
Section: Dovepressmentioning
confidence: 99%
See 3 more Smart Citations